2004
DOI: 10.1097/00004872-200402000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular target organ damage in essential hypertensives with or without reproducible nocturnal fall in blood pressure

Abstract: Despite similar clinic and 48-h BP values, never-treated hypertensive patients with a persistent non-dipper pattern showed a significantly greater extent of cardiac structural alterations compared with subjects with a reproducible dipping pattern, but not those with a variable BP nocturnal profile. A non-dipping pattern diagnosed on two concordant ABPM periods instead of a single monitoring therefore represents a clinical trait associated with more pronounced cardiac abnormalities. Finally, in non-dipping midd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
140
4
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(157 citation statements)
references
References 34 publications
5
140
4
5
Order By: Relevance
“…31 The reasons of the prognostic superiority of night-time over daytime BP are not clear, although one hypothesis is that the prognostic value of diurnal BP may be reduced by its excessive variability compared to the nocturnal period.…”
Section: Discussionmentioning
confidence: 99%
“…31 The reasons of the prognostic superiority of night-time over daytime BP are not clear, although one hypothesis is that the prognostic value of diurnal BP may be reduced by its excessive variability compared to the nocturnal period.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, a large number of cross-sectional studies in hypertensive subjects have established an almost constant association between nocturnal BP phenotypes with cardiac adaptations including abnormal LV mass and geometry. 7,8,12,21,22 In addition, nondippers and those with hypertensive nocturnal BP values demonstrated impaired LV diastolic function, abnormal aortic root diameters and left atrium structural properties compared with dippers and those with normotensive nocturnal BP levels, respectively. 23,24 However, other studies have reported no difference in cardiac adaptations among dippers and nondippers, [25][26][27][28] whereas nocturnal hypertension was constantly related to LV mass, an issue not addressed by absolute nocturnal systolic and diastolic BP.…”
Section: Cardiac Adaptationsmentioning
confidence: 96%
“…With respect to the latter, there is an ongoing debate for the reduced reproducibility of ABPM measurements possibly resulting in misclassification of the dipping/nondipping status. 12 Furthermore, shift and nighttime work constitute a further issue not addressed by the design of the majority of ABPMoriented studies, and finally, variations in nocturnal body position and diurnal physical activity may affect nighttime and daytime BP, respectively. 13 The nondipping profile is frequently accompanied by enhanced nocturnal BP; thus, the discrimination between them might be an eternal unfulfilled target to address.…”
Section: Dipping Pattern Versus Nighttime Bpmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] On the other hand, as ABP is affected by various internal and external environmental factors on a particular day, the reproducibility of its mean value is inferior to that of home BP, [23][24][25] and the reproducibility of circadian BP variations based on ABPM is not enough. [26][27][28][29] Table 1 summarizes the characteristics of home BP compared with clinic BP and ABP. 30 …”
Section: Introductionmentioning
confidence: 99%